SUMBER DAYA ALAM DI KAWASAN PESISIR PULAU NUSA PENIDA DAN SEKITARNYA, KABUPATEN KLUNGKUNG, NUSA TENGGARA BARAT - P. Astjario (Pusat Survei Geologi, 2008)
Nusa Penida, Lembongan and Ceningan islands consist of Pliocene reef limestone at some place. The limestone forms dolomite characterized, white in color and soft. The southern coastal of Nusa Penida Island exposed bedded limestone, re-crystallization and weakened. Karts topography widely spread in this island, however it has been eroded.The coastal zone of Nusa Penida, Lembongan and Ceningan islands have been utilized for sea water tourism and sea grass cultivation. However, these areas still have various renewable energy resources which have not yet been developed optimally. In order to support Renewable Energy Park Programs in Nusa Penida, the current energy of Ceningan strait can be used for electricity power energy.Â Keywords: coastal, renewable energy, current and limestone.